Welfare regimes and macroeconomic regime constellations: explaining the Scandinavian anomaly. (30th March 2010) - Sauer, Thomas; Vogel, Lena
Since the early 1990s, the Scandinavian countries have recovered from one of the most severe crises of any Organisation for Economic Cooperation and Development (OECD) country ever, returning to a 'high road' growth path and also succeeding in terms of macroeconomic stabilisation indicators. To explain the causes for this coincidence of macroeconomic growth and stability, we propose a theory of macroeconomic resilience. We merge different theoretical strands into a joint approach of Macroeconomic Regime Constellations (MERCs) and Welfare Regime Constellations (WERCs). In the econometric part of our inquiry, we estimate Structural Vector Autoregressions (SVARs) to analyse the existence and consistency of MERCs in Sweden, Finland and Denmark.